Nutritional Evaluation, Functional Properties and Anti-Nutritional Factors of Macrobra chium rosenbergii, an Underutilized Animal (Biological Sciences - PJSIR, 2007)
The proximate, nutritionall y val uable mi nerals , functional and anti-nutri tional factors of Macrobrachium rosenbergii were determined i n the laboratory for h uman consumption. Resul ts i ndicated a high protei n content (68.88 ± 0.56%), ash ( 1 5.33 ± 0. 14%), moisture (9.37 ± 0.03%), fat (5.36 ± 0.0 I %) and carbohydrate (1 .06 ± 0.00%), while fi bre was not detected. Protei n solubi lity was pH dependent with mi n i m um and max imum protei n sol ubi l ities at pH  2, pH 6  and pH 1 1 . Nutritionally val uabl e mineral analyses showed that M. rosenbergii contains phosphorus ( 126.1 8 ± 0.032 mg/ I 00 g), magnesi um (86.44 ± 0.10 mg/I 00 g), potassium (64.24 ± 0.20 mg/ 1 00 g), sodium (57.53 ± 0.1 5 mg/I 00 g), calcium(49.54 ± 0.1 1 mg/ 100 g), i ron (7.20 ± 0.02 mg/ I 00 g), manganese (0.89 ± 0.0 I mg/ I 00 g) and zi nc (0.69 ± 0.01 mg/I 00 g). Copper, cobal t, lead , nickel and chromi um were not detected. The sample had a mini mum gelation concentration of (8.5 ± 0. 1 0%), water absorption capacity (345.00 ± 0.30%), oil absorption capacity (521 .36 ± 0.1 2%), foaming capacity(15.00 ± 0.05%), foaming stabi lity (2.20 ± 0.01 %, emulsion capaci ty (22.62 ± 0.03%) and emulsion stabi l ity (45 .50 ±0.15). Three anti-nutrients were determined : ph ytic acid was 4.00 ± 0.0 I mg/I 00 g, oxalate 1 .05 ± 0.00 mg/ I 00 g while tannin was not detected .